How do you factor the expression x2 + 2x -3?

We need to factorise the given equation

Given equation

x2 + 2x-3

Let us try factorizing this polynomial using splitting the middle term method.

Factoring polynomials by splitting the middle term:

We need to find two numbers ‘a’ and ‘b’ such that a + b =2 and ab = 3.

On solving this we obtain, a = 3 and b = -1

Thus, the above expression can be written as:

x2 + 2x-3

= x2 +3x -x – 3

= x(x + 3) -1(x + 3)

= (x + 3)(x -1)

Thus, x+3 and x-1 are the factors of the polynomial x2 + 2x-3.

Leave a Comment

Your email address will not be published. Required fields are marked *

BOOK

Free Class